EFEKTIVITAS TEKNIK SOSIODRAMA MELALUI BIMBINGAN KELOMPOK UNTUK MENGURANGI PERILAKU AGRESIF VERBAL SISWA SMP - Winarlin, Retno; Lasan, Blasius Boli; Widada, Widada (Jurnal Kajian Bimbingan dan Konseling, 2016)
This research aims to discover the effectiveness of group-counseling sociodramas to reduce verbal aggressive acts of junior High School students. The research design used is quasi-experiment, which is one Group Pre-test Post-test Design. The treatment given to experimental group is sosiodramas. Researcher does a measurement before and after the treatment given to see whether there is a change shown by research subjects. the subjects are 16 eight-graders of SMP Negeri 15 Malang with high verbal aggressiveness scores. The pre-test and the post-test is in the form of verbal aggressive acts inventory which are done once each. Treatment giving is done in five meetengs. The analysis result using SPSS 16 for windows, Wilcoxon Signed Ranked Test score shows different value (Z= -3.517a) with 0.000 (P= 0.000 < 0,05), which proves group-counseling sociodramas are effective to reduce verbal aggressive acts of Junior High School students.